Getting straight to the source: who evaluates the leadership skills of premiers in Canada and Australia?. Issue 1 (2nd January 2023) - Auer, Meagan; Trimble, Linda; Curtin, Jennifer; Reist, Rissa; Wagner, Angelia; Woodman, V. K. G.
ABSTRACT: Journalists have the power to shape the public's perception of new premiers. They also share that power with the sources they interview. Sourcing is therefore important when making claims about the news media's role in reproducing gender biases in representations of political leaders. We examine the question of sourcing through an analysis of newspaper coverage of 22 newly elected women and men subnational government leaders in Australia and Canada to answer the following questions. How do news writers rely on sources in evaluations of new premiers? To what extent do they employ different patterns of sourcing and are these sourcing patterns gendered? We focus on two pairs of leadership traits that dominate news coverage of premiers in the first week: strength/weakness and competence/incompetence. We find that journalists use unattributed assessments rather than sources when evaluating premiers' skills and abilities, but when sources are cited, these are usually elite men.